Germline genome-editing research and its socioethical implications - Ishii, Tetsuya (Trends in molecular medicine, 2015)
•Calls for a moratorium on human germline genome editing have been carefully examined.•In vitro research is not necessarily subject to moratorium.•Most importantly, the socioethical implications of the research need to be widely debated.•Public dialogue is crucial to shape social attitudes towards germline editing. Genetically modifying eggs, sperm, and zygotes (‘germline’ modification) can impact on the entire body of the resulting individual and on subsequent generations. With the advent of genome-editing technology, human germline gene modification is no longer theoretical. Owing to increasing concerns about human germline gene modification, a voluntary moratorium on human genome-editing research and/or the clinical application of human germline genome editing has recently been called for. However, whether such research should be suspended or encouraged warrants careful consideration. The present article reviews recent research on mammalian germline genome editing, discusses the importance of public dialogue on the socioethical implications of human germline genome-editing research, and considers the relevant guidelines and legislation in different countries.